IMPLEMENTASI KONSEP PENDIDIKAN AKHLAK ABDULLAH NASHIH ‘ULWAN DALAM MEMBENTUK KARAKTER SISWA SMP NEGERI 2 KUTA BLANG BIREUEN - Hasanah, Hasanah (Journal of Contemporary Indonesian Islam, 2024)
This study examines the implementation of Abdullah Nashih 'Ulwan's concept of moral education in shaping the character of students at SMP Negeri 2 Kuta Blang Bireuen.  The formation of noble morals through character education should be able to form commendable behaviors and noble morals in students. the type of research is qualitative research with a descriptive research approach. The purpose of this research is to explain the concept of Akhlak Education Abdullah Nashih 'Ulwan. The results of this study indicate that. 1) The concept of Abdullah Nashih 'Ulwan's moral education used is education by example, education by habituation, education by advice, education by attention and monitoring and education by appropriate punishment. 2) The implementation of Abdullah Nashih 'Ulwan's five concepts of moral education is carried out during the teaching and learning process, extracurricular activities and all the time when students are at school, the efforts made by teachers in implementing the concept of 'Ulwan's moral education are teachers coming to school on time, greeting kindly when students come, giving good advice, paying attention to student conditions and giving proper punishment if students make mistakes.